Why Are There So Few? A Note from Mathematics and the Fear of Mathematics as Predictors of Choosing Science and Technical Studies by Female Secondary School Graduates - Turska, Dorota (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The article makes an attempt to explain a phenomenon of a small representation of women on science/ technical degree courses (Why are there so few?). The study focuses on the "paradox" dimension of the phenomenon, showing that female students do not take up such studies also if they have high achievements in mathematics. It is suggested (Trusz 2015) that the reason for that is, amongst others, the fear of mathematics. Own research was carried out in order to empirically show the school notes and the fear of mathematics in the role of predictors for choosing science/technical studies by the secondary school graduates (in relation to their schoolmates). The obtained data indicate that generally, in the case of the female students the role of a positive predictor of the choice is the highest maths note, but the fear of testing the mathematics knowledge is a strong negative predictor. A detailed analysis of the constellation of those both variables in the context of the predicted probability of choosing the science/technical studies by the highest evaluated female students was carried out. The results show that a subjective interpretation of the fear, and not the extent of the fear, has a significant importance. Discussing the results of own research, a reference was made to S.J. Correll’s concept of gender status (2004).